Modular prevention of heart disease following acute coronary syndrome (ACS) [ISRCTN42984084] - Briffa Tom; Ellis Elizabeth; Redfern Julie; Freedman SB (BMC Cardiovascular Disorders, 2006)
Abstract Background Coronary heart disease (CHD) is a major cause of morbidity and mortality in Australia and it is recommended that all persons with unstable angina (UA) or myocardial infarction (MI) participate in secondary prevention as offered in cardiac rehabilitation (CR) programs. However, the majority of patients do not access standard CR and have higher baseline coronary risk and poorer knowledge of CHD than those persons due to commence CR. The objective of this study is to investigate whether a modular guided self-choice approach to secondary prevention improves coronary risk profile and knowledge in patients who do not access standard CR. Methods/Design This randomised controlled trial with one year follow-up will be conducted at a tertiary referral hospital. Participants eligible for but not accessing standard CR will be randomly allocated to either a modular or conventional care group. Modular care will involve participation in individualised modules that involve choice, goal-setting and coaching. Conventional care will involve ongoing heart disease management as directed by the participant's doctors. Both modular and conventional groups will be compared with a contemporary reference group of patients attending CR. Outcomes include measured modifiable risk factors, relative heart disease risk and knowledge of risk factors. Discussion We present the rationale and design of a randomised controlled trial testing a modular approachfor the secondary prevention of coronary heart disease following acute coronary syndrome.